Comparative study of Coral Conversion, Part 2: Microstructural evolution of calcium phosphate - (:unkn) unknown (SPRINGER, 2015)
Calcium phosphate materials can be easily produced by a number of wet chemical methods that involve both acidic and basic environments. In our previous study, we investigated calcium phosphates such as monetite (DCPA), hydroxyapatite (HAp) and whitlockite which were successfully produced by mechano-chemical method from corals obtained from the Great Barrier Reef. It was observed that a number of synthesis factors such as the pH of the environment, the reaction temperature and the chemistry influenced the crystal size formed. A number of theories have been suggested on the mechanisms of crystal formation; however, very few mechanisms have been universally accepted. The present work was aimed to explore the evolution of crystalline calcium phosphate and their morphology with respect to the pH of the environment and reaction time. Conversion of coral to calcium phosphates was carried out with stoichiometric amount of required H3PO4 or (NH4)(2)HPO4, to obtain hydroxyapatite or tricalcium phosphate (TCP) phases. The acidic or basic solution was added, drop wise, at a rate of 2 mL min(-1), to 6 g of coral powder suspended in 300 mL of distilled water at 80 +/- 0.5 degrees C on a hot plate with magnetic stirrer. The pH of reaction was monitored. Crystal morphology and the phases were identified by XRD, FTIR, and SEM studies. It was observed that under acidic conditions (H3PO4), dissolution and then precipitation influences the crystal morphology and transition from plate like to rod like hydroxyapatite structure. During the first hour of the dissolution a monetite and hydroxyapatite mixture precipitates and then the full conversion to hydroxyapatite is observed. However under basic conditions (NH4)(2)HPO4), pH is only marginally changed within the environment and just surface conversion of the calcium carbonate structure of coral to hydroxyapatite and a very small amount of tri-calcium phosphate is observed. The mechanism can be classified as the solid state topotactic ion-exchange reaction mechanism.
Keywords: Hydroxyapatite; calcium phosphate; pH; Mechano-chemical conversion; morphology; HYDROXYAPATITE; ACID; PRECIPITATION